ADAPTIVE SELLING BEHAVIOUR: A STUDY AMONG SALESPERSON IN PHARMACEUTICAL INDUSTRY - Kok Leong Wong,; Cheng Ling Tan, (Asian Academy of Management Journal, 2018)
Sales management of today is facing challenging issues of sales force management in order to achieve the desired firm’s business performance. A firm’s business performance is closely associated to how effective the sales force is in performing their selling tasks. As salespersons need to face different customers and engage in different sales situations, salespersons must be flexible and be able to adapt their selling styles in all different situations. Salespersons’ behaviour in adapting their selling approaches is known as adaptive selling behaviour. The ability of salespersons in performing their selling tasks hinges on their capability in practicing adaptive selling behaviour during and across the sales interactions with customers. This study focuses on the managerial practices of control and empowerment, and examines their simultaneous influence on salesperson’s adaptive selling behaviour. This study was conducted on a sample of pharmaceutical salespersons in Malaysia, whose customers are healthcare professionals. Nine pharmaceutical firms participated in the survey with a total of 154 responses received. Results revealed that control practice of activity control and empowerment practices of promoting participation in decision-making, expressing confidence, and providing autonomy had significant relationships with salesperson’s practice of adaptive selling behaviour. Implications, limitations of the research, and improvements for future studies were discussed.